A study of common defect on precast concrete building / Mohd Asyraf Mohammad Samsuri - Mohammad Samsuri, Mohd Asyraf (Faculty Architecture, Planninng and Surveying, 2014)
Industrialised Building System (IBS) has been introduced in Malaysia since early 1960s when Ministry of Housing and Local Government of Malaysia visited several European countries and evaluate their housing development program (Thanoon et al, 2003). In the 1960s, precast concrete system was often misinterpreted with negative meaning. The lack of design such as the need for wet toilets and bathrooms lead to problem of leakage. Besides that, the most common problems were the connection between the beam to column and column to base (Rahman and Omar, 2006). In this study, the first objective is to identify the defects on precast concrete building. Then, the second objective is to determine the factors contributing towards the defects occurred. Lastly, the third objective of this study is to recommend the approach that should be taken to prevent the defects occurred. From the research, the defects occurred only minor defects and no major defects. The researcher found that mostly the defects occur is hairline crack, either at wall, column and jointing between the column and beam on both case study area. Besides that, the other defects occur is peeling paint, spalling, dampness, fungi and others. It is very important to the stakeholder such as easy to the stakeholder identify the defects occurred on that building. Besides that, the stake holder easily to classify the factors that contribute the defects to ensure and prevent the defects may occur in future.